Pengaruh Debt To Equity Ratio (DER) Dan Debt To Asset Ratio (DAR) Terhadap Harga Saham Pada Perusahaan Tekstil Dan Garmen Di Bei Tahun 2017-2020 - Kurnianti, Mega Ayu; Nurmala, Nurmala; Dewi, Anita Kusuma (Jurnal Ekonomika Dan Bisnis (JEBS), 2022)
Stock prices the price of a share which is determined in accordance with the supply and demand of the relevant shares at the time of supply. The prevailing stock prices the capital market is usually determined by market participants who trade their shares. Debt to equity ratio (DER) is a comparison where how much own capital can be used as collateral for debt, Debt to Asset Ratio (DAR) is a ratio to measure how much company assets are financed by creditors. The population in this study are textile and garment companies that are registered and active on the Indonesia Stock Exchange (IDX) during the 2017-2020 period, obtained as many as 23 companies and 23 of them can be sampled with a total of 70 data after data transformation taken from certain criteria. The data used is quantitative data with data collection methods in the form of documentation methods. The results obtained from this study are, the Debt to Equity Ratio (DER) variable has an effect on stock prices while the Debt to Asset Ratio (DAR) variable has no effect on stock prices.